Effect of pulmonary rehabilitation programme including either O2 inhalation or noninvasive ventilation in patients with chronic obstructive pulmonary disease - *Basma Elsaeed Saad Elmorshidy; Mohamed Gamal Amer Elkholy; Hanan Mohamed Elsaadany; Mansour Youssef Mohamed; Ragia Samir Sharshar; Hoda Mokhtar Bahr (Canadian Journal of Respiratory Therapy, 2023)
Background